MENUNJUKKAN KEBUTUHAN DAN KONTRIBUSI DARI RUANG HIJAU PERKOTAAN DI KOTA METROPOLITAN - Anggara, Aang (Badan Penelitian dan Pengembangan Daerah Provinsi Jawa Barat, 2024)
The role and contribution of urban green space have become crucial. In addition to serving as a space to maintain environmental quality and improve people's living conditions, urban green space also serves a purpose in the transformation of an urban region. This study aims to examine what factors influence the increase in the amount of UGS in Bekasi Municipality as a Metropolitan city. The data were collected from Spatial Planning Office and Central Bureau of Statistics in 2013- 2022. Using Multiple Regression techniques, this research explores the association of variables in terms of the necessity for UGS. The result of this study shows that the population have a positive correlation but no significant impact on the total area of UGS. The total area of residential has a positive and significant impact on UGS, while the growth of the real estate sector has a negative impact and is not significant on the total area of UGS in Bekasi City. With the increasingly limited land area, the government of Bekasi Municipality should pay attention to the availability of existing land so that it can be used for urban green areas.